Maggot Cultivation Business Development Strategy at the Siliwangi Unit Waste Bank - Gandhy, Abel; Gursida, Hari; Sunarta, Ketut; Marota, Rochman; Zaini, Oktori Kiswati (Jurnal Ilmiah Manajemen Kesatuan, 2024)
Research on maggot farming business development strategies is still relatively limited. This research is important because it provides recommendations for business strategies that can maximize the development of the company's business. The Black Soldier Fly (BSF) larval cultivation business at the Siliwangi Unit Waste Bank has the potential to grow bigger. Business strategy provides sustainable planning to manage resources comprehensively and identify conditions for achieving future business success and gaining maximum profit. This research was conducted at the Siliwangi Unit Waste Bank, Bogor City, which was selected purposively because the BSF larval cultivation activities there have the potential to be developed further. This research uses quantitative and qualitative data sourced from primary and secondary data. Primary data were collected through surveys and direct observations by researchers, while secondary data were obtained from institutional reports, journals, books, news articles, and other library sources. Internal environment (IFE) and external environment (EFE) analysis were conducted to identify factors that could influence business success. The results of this analysis were used in the Internal-External Matrix (IE) which produced three main strategies: Growth, Stability, and Reduction Strategies. These strategies are the basis for developing the maggot cultivation business at the Siliwangi Unit Waste Bank.